Wind‐driven exchanges between two basins: Some topographic and latitudinal effects. Issue 9 (18th September 2013) - Yang, Jiayan; Lin, Xiaopei; Wu, Dexing
Key Points Flows between the open ocean and marginal sea is restricted by topography Island rule does not apply to flows through shallow channels friction promotes flows over sill